Controlling of the constitutional judiciary over the elections of members of House of Representatives - Haider Hashem , Researcher. Tabarak; Zaki Nouri, Assist . Prof . Suha (Basra studies journal, 2024)
The supervisory jurisdiction of the constitutional judiciary embodies the most important functions of the constitutional judiciary ever, as it is the justification for its existence and the basis for its establishment in general; to establish and activate the principle of the supremacy of the constitution, because it is a jurisdiction that works to ensure the commitment of public authorities to constitutional rules, when exercising their constitutionally stipulated jurisdictions, by tracking their actions and correcting their deviations, and ensuring that none of them violates the constitutional powers of the other authority, therefore the Iraqi constitution formed a judicial body to consider and adjudicate disputes resulting from the course of the electoral process to ensure the constitutionality of the electoral process until the role of the Federal Supreme Court comes, as it is competent to consider electoral appeals and ratify the results of parliamentary elections, which is the last stage in the electoral process.